1987
DOI: 10.1002/art.1780300211
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan‐induced arthritis in balb/c mice

Abstract: Immunization with chondroitinase ABC-digested fetal human cartilage proteoglycan and Freund's complete adjuvant induced polyarthritis and ankylosing spondylitis in female BALB/c mice. The initial external symptoms of the joint inflammation were swelling and redness. This was associated with edema of the synovium and periarticular tissues and gross proliferation of cells, which reached a peak during weeks 7-9 of the experiment. Mononuclear cell infiltration, with perivascular concentration and occlusion of smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
170
2
3

Year Published

1987
1987
1999
1999

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 266 publications
(179 citation statements)
references
References 34 publications
4
170
2
3
Order By: Relevance
“…We have reported that female BALBk mice that have been immunized with fetal human proteoglycan in adjuvant develop progressive polyarthritis with ankylosing spondylitis (22). Clinical studies, including radiographic analyses and scintigraphic bone scans, together with the histopathologic study of diarthrodial joints and spine, showed many similarities to both rheumatoid arthritis and ankylosing spondylitis.…”
Section: Immunity To Cartilage Proteoglycans In Balb/c Mice With Progmentioning
confidence: 99%
See 3 more Smart Citations
“…We have reported that female BALBk mice that have been immunized with fetal human proteoglycan in adjuvant develop progressive polyarthritis with ankylosing spondylitis (22). Clinical studies, including radiographic analyses and scintigraphic bone scans, together with the histopathologic study of diarthrodial joints and spine, showed many similarities to both rheumatoid arthritis and ankylosing spondylitis.…”
Section: Immunity To Cartilage Proteoglycans In Balb/c Mice With Progmentioning
confidence: 99%
“…The arthritis starts as a polyarticular synovitis, including a spondylitis, which becomes progressive and produces cartilage and bone erosion within the joint, with stiffness and deformities in diarthrodial joints, resorption of growth plates and intervertebral discs, and ankylo- * Fetal human proteoglycan (PG) monomer digested with chondroitinase ABC (chase ABC) was used to determine the antibody concentration, by solid-phase radioimmunoassay, on day 28 of immunization, and to determine the stimulation index during weeks 16-20 of immunization. Data from groups 1-13 have been presented in part elsewhere (22). All mice were female, except for those in group 9, which were male.…”
Section: Immunity To Cartilage Proteoglycans In Balb/c Mice With Progmentioning
confidence: 99%
See 2 more Smart Citations
“…bovine, proteins [8][9][10]. The major proteoglycan of the joint, aggrecan, has also been shown to induce arthritis in certain mouse strains, if given in a heterologous (human) form [11]. The induction of arthritis with heterologous cartilage proteins may be a way to circumvent the strong tolerance of T cells specific for cartilage proteins [12].…”
Section: Introductionmentioning
confidence: 99%